1989
DOI: 10.4315/0362-028x-52.7.500
|View full text |Cite
|
Sign up to set email alerts
|

Recommended Assay for Treatment of Chicks to Prevent Salmonella Colonization by ‘Competitive Exclusion’

Abstract: An assay is described for evaluating live-culture treatment material that may be given orally to chicks to prevent intestinal colonization by non-host-specific salmonellae. Both pre-treated and control chicks are challenged with ca 104 salmonellae/chick, using a strain bearing an antibiotic resistance marker. Chicks are examined 5 d after challenge to determine both the proportion of positive birds in treated and control groups and the levels of Salmonella in the caeca of infected individuals. The efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 0 publications
0
33
0
2
Order By: Relevance
“…O Fator de infectividade foi determinado através da leitura das placas, onde se calculou a relatividade do número de colônias, por amostra de 10 aves e o Fator de Proteção é o componente relativo ao número do fator de infectividade. O método utilizado foi o descrito por Mead et al (1989). Utilizou-se placas de petri, com meio de cultura MacConkey (MERK) para o isolamento das cepas; meio BHI ou caldo nutriente, no enriquecimento das culturas; água peptonada 0,10%, para o isolamento das cepas; PBS 0,1 M pH 7, tampão fosfato salino na diluição das amostras; meio XLD (Gram-negativo) específico para a identificação das salmonelas e álcool a 70%, na desinfecção do local de coleta.…”
Section: Tabelaunclassified
“…O Fator de infectividade foi determinado através da leitura das placas, onde se calculou a relatividade do número de colônias, por amostra de 10 aves e o Fator de Proteção é o componente relativo ao número do fator de infectividade. O método utilizado foi o descrito por Mead et al (1989). Utilizou-se placas de petri, com meio de cultura MacConkey (MERK) para o isolamento das cepas; meio BHI ou caldo nutriente, no enriquecimento das culturas; água peptonada 0,10%, para o isolamento das cepas; PBS 0,1 M pH 7, tampão fosfato salino na diluição das amostras; meio XLD (Gram-negativo) específico para a identificação das salmonelas e álcool a 70%, na desinfecção do local de coleta.…”
Section: Tabelaunclassified
“…To standardize ST challenges, Mead et al (1989) termed this value the "infection factor" (IF) and introduced another criterion calculated by dividing the IF value of the untreated group by that of the CE product-treated group, which they designated the "protection factor" (PF). Mead et al, suggested that cultures with PF values <4 would be insufficient to mitigate Salmonella infection in commercial poultry flocks.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that tests of one or two weeks duration (Mead et al, 1989) may not be sufficient to evaluate the effectiveness of competitive exclusion products.…”
Section: Discussionmentioning
confidence: 99%